(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
The excavations conducted by the University of Milan for almost thirty years at Calvatone (CR), directed by Prof. Maria Teresa Grassi, have been focused on bringing to light the remains of the Roman vicus of Bedriacum, which has been an important strategic and commercial centre on the Via Postumia. Since 2011 fieldworks and campaigns devoted to the study of artefacts have been accompanied by educational activities in order to valorize the historical and archaeological significance of the site and make the discoveries accessible to a wider public.